Routinised recognition and anxiety: Understanding the deterioration in Sino-Japanese relations. Issue 4 (11th January 2016) - Gustafsson, Karl
Abstract: Why do interstate relations deteriorate and become conflictual, even under conditions where one might expect improved ties? The article seeks an answer to this question through a case study of the deterioration in Sino-Japanese relations in the twenty-first century, which took place despite the existence of several factors that might be thought likely to have led to an improvement. Existing theoretical approaches cannot fully explain this puzzle. The article argues that such deteriorations can result from disruptions to states' reciprocally performed routinised recognition, and identifies three mechanisms through which these can occur. To facilitate this argument, the article draws on scholarship on relational identity, recognition, and ontological security to develop a theory of identity construction that takes account of how self and other routinise the ways in which they recognise each other and how they react to the other's representational practices.